2017
DOI: 10.5511/plantbiotechnology.16.1201a
|View full text |Cite
|
Sign up to set email alerts
|

MYB-mediated upregulation of lignin biosynthesis in <i>Oryza sativa</i> towards biomass refinery

Abstract: Lignin encrusts lignocellulose polysaccharides, and has long been considered an obstacle for the efficient use of polysaccharides during processes such as pulping and bioethanol fermentation. However, lignin is also a potential feedstock for aromatic products and is an important by-product of polysaccharide utilization. Therefore, producing biomass plant species exhibiting enhanced lignin production is an important breeding objective. Herein, we describe the development of transgenic rice plants with increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 52 publications
(68 reference statements)
3
26
0
Order By: Relevance
“…3D), S lignin signals were clearly depleted over G lignin signals in the fnsII mutant cell wall spectra. Besides the typical aromatic signals from the monolignol-derived lignins, the HSQC spectra of wildtype cell walls displayed the characteristic set of aromatic signals from lignin-bound tricin units (T); the chemical shifts of all the C-H correlations from the flavone aromatic system (T 3 , T 8/6 , and T 29/69 ) are in total agreement with literature data (Del Río et al, 2012;Lan et al, 2015;Koshiba et al, 2017). In contrast, all these tricin signals were strikingly depleted to undetectable levels (less than 1%) in the spectra of fnsII mutant cell walls (Fig.…”
Section: Two-dimensional Nmr Analysis Of Osfnsii-knockout Mutant Ricesupporting
confidence: 85%
See 1 more Smart Citation
“…3D), S lignin signals were clearly depleted over G lignin signals in the fnsII mutant cell wall spectra. Besides the typical aromatic signals from the monolignol-derived lignins, the HSQC spectra of wildtype cell walls displayed the characteristic set of aromatic signals from lignin-bound tricin units (T); the chemical shifts of all the C-H correlations from the flavone aromatic system (T 3 , T 8/6 , and T 29/69 ) are in total agreement with literature data (Del Río et al, 2012;Lan et al, 2015;Koshiba et al, 2017). In contrast, all these tricin signals were strikingly depleted to undetectable levels (less than 1%) in the spectra of fnsII mutant cell walls (Fig.…”
Section: Two-dimensional Nmr Analysis Of Osfnsii-knockout Mutant Ricesupporting
confidence: 85%
“…Subsequently, extensive surveys have revealed that tricin-bound lignins exist abundantly, particularly in the monocot family Poaceae, which comprises grasses including cereals. They also have been found in some commelinid monocot families outside Poaceae, such as Arecaceae (palms) and Bromeliaceae (pineapples and relatives), the noncommelinid family Orchidaceae (the orchids), particularly in the genus Vanilla, and also in certain dicots (Rencoret et al, 2013;Wen et al, 2013;Del Río et al, 2015;Lan et al, 2015Lan et al, , 2016aLan et al, , 2016bKoshiba et al, 2017).…”
mentioning
confidence: 96%
“…A few previous studies have also implicated the possible existence of such alternative monolignol pathway(s) or metabolic pool(s) associated with the grass‐specific lignin substructures. For example, heterologous expression of a lignin‐associated MYB transcriptional factor in rice increased lignin content mainly by enriching grass‐specific lignin subunits, including p CA and tricin (Koshiba et al ., ). Barros et al .…”
Section: Discussionmentioning
confidence: 97%
“…In addition, S lignins may be beneficial to the conversion of lignin‐derived aromatic chemicals because S lignins produce higher yields of aromatic monomers in chemical degradations compared with yields from G lignins (Rinaldi et al ., ; Shuai et al ., ; Lan et al ., ). On the other hand, G lignins may enhance the combustion properties of biomass as they exhibit lower degrees of lignin methoxylation and higher frequencies of carbon–carbon inter‐monomeric linkages, and therefore may show greater heating values during biomass combustion compared with those of S lignins (Koshiba et al ., ; Takeda et al ., ; Umezawa, ). Overall, we consider that an advanced understanding of lignin biosynthesis unique to grasses will increase our capability to manipulate grass biomass for sustainable production of biofuels and biomass‐based materials.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation